2001
DOI: 10.1002/bies.1100
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic DNA bends: an organizer of local chromatin structure for transcription

Abstract: DNA with a curved trajectory of its helix axis is called bent DNA, or curved DNA. Interestingly, biologically important DNA regions often contain this structure, irrespective of the origin of DNA. In the last decade, considerable progress has been made in clarifying one role of bent DNA in prokaryotic transcription and its mechanism of action. However, the role of bent DNA in eukaryotic transcription remains unclear. Our recent study raises the possibility that bent DNA is implicated in the "functional packagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 87 publications
3
40
0
Order By: Relevance
“…Both cis-acting regulatory sequences near ori and proteins acting in trans appear to have an important function in controlling replication (4,5,14,29,45,50,61). Bent DNA may facilitate interaction between cis-DNA elements and trans-acting factors by organizing local chromatin infrastructure (44). Our data are consistent with the reported role that chromatin structure and nucleosome destabilization play in DNA replication (1,19).…”
Section: Containing the Sequences 5ј-(a/t)(a/t)a‫3-ء‬ј And 5ј-(a/t)(gsupporting
confidence: 87%
“…Both cis-acting regulatory sequences near ori and proteins acting in trans appear to have an important function in controlling replication (4,5,14,29,45,50,61). Bent DNA may facilitate interaction between cis-DNA elements and trans-acting factors by organizing local chromatin infrastructure (44). Our data are consistent with the reported role that chromatin structure and nucleosome destabilization play in DNA replication (1,19).…”
Section: Containing the Sequences 5ј-(a/t)(a/t)a‫3-ء‬ј And 5ј-(a/t)(gsupporting
confidence: 87%
“…A high hierarchical level of gene regulation is represented by changes in the DNA conformation, such as DNA supercoiling or the presence of intrinsically curved DNA (14,33). In studies with mutants it has been shown that the maximal abundance of proteins in a set of 88 proteins investigated occurred at supercoiling levels below that of the wild type, and others were most abundant with elevated levels of negative superhelices (46).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that DNA curvature is important in many basic genetic processes (for reviews, see refs. [9][10][11][12]. In bacterial promoters, curved DNA structures have a range of functions: facilitating RNA polymerase binding to the promoter, promoting the transition from closed to open promoter complexes, and enhancing binding of transcription factors.…”
Section: Introductionmentioning
confidence: 99%